Forced displacements, reception policies: portuguese state in the case of refugees - Ribeiro, Renata Maria Franco (2020)
Our work takes place in the migratory context in mid-2013 to 2016, with the perspective of understanding how the Policies of Reception and Integration are articulated in the case of Refugees in the Portuguese State, as the main entry of these subjects by Greece and Italy. We are interested in analyzing what drove the state Portugal to offer the largest number of places for the reception of refugees as a member state of the European Union. And how the integration of these subjects takes place. For data collection and the methodological path, we opted for documentary sources and a bibliographic survey of the last five years regarding the issue of refugees in Europe and specifically in Portugal, and consult official websites and platforms. The starting question is: what are the strategies of the Portuguese state in the perspective of integration, insertion of individuals with refugee status? Our theoretical basis: Silvestre (2011), Ribeiro (2017), Carapeto (2017), Malpique (2018).